Sectional relationships in the genus Musa L. inferred from PCRRFLP of organelle DNA sequences - Nwakanma, D.C.; Pillay, M.; Okoli, B.E.; Tenkouano, A. (Springer, 2003)
The objective of this study was to construct a molecular phylogeny of the genus Musa using restriction-site polymorphisms of the chloroplast (cpDNA) and mitochondrial DNA (mtDNA). Six cpDNA and two mtDNA sequences were amplified individually in polymerase chain reaction (PCR) experiments in 13 species representing the four sections of Musa. Ensete ventricosum (W.) Ch. was used as the outgroup. The amplified products were digested with ten restriction endonucleases. A total of 79 restriction-site changes were scored in the sample. Wagner parsimony using the branch and bound option defined two lines of evolution in Musa. One lineage comprised species of the sections Australimusa and Callimusa which have a basic number of x = 10 chromosomes, while most species of sections Eumusa and Rhodochlamys (x = 11) formed the other lineage. Musa laterita Cheesman (Rhodochlamys) had identical organellar genome patterns as some subspecies of the Musa acuminata Colla complex. The progenitors of the cultivated bananas, M. acuminata and Musa balbisiana Colla, were evolutionarily distinct from each other. Musa balbisiana occupied a basal position in the cladogram indicating an evolutionarily primitive status. The close phylogenetic relationship between M. laterita and M. acuminata suggests that species of the section Rhodochlamys may constitute a secondary genepool for the improvement of cultivated bananas.